2019
DOI: 10.1136/bmjopen-2018-023859
|View full text |Cite
|
Sign up to set email alerts
|

Relating knowledge, attitude and practice of antibiotic use to extended-spectrum beta-lactamase-producing Enterobacteriaceae carriage: results of a cross-sectional community survey

Abstract: ObjectivesTo study the correlation between knowledge, attitude and practices (KAP) of antibiotic consumption with epidemiology and molecular characteristics of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) carriage, in order to identify modifiable factors and public health interventions to reduce prevalence of multidrug-resistant organism colonisation in the community.DesignCross-sectional questionnaire of KAP towards antibiotic use and collection of stool samples or rectal swabs. ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
3
14
2
Order By: Relevance
“…Several studies have revealed that antibiotics are more likely to be prescribed under patients' pressure [25]. Another study revealed widespread misconceptions about the utility of antibiotics for viral infections [26]. This is consistent with the findings of a global survey conducted by the world health organization (WHO) in 2015 [27].…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have revealed that antibiotics are more likely to be prescribed under patients' pressure [25]. Another study revealed widespread misconceptions about the utility of antibiotics for viral infections [26]. This is consistent with the findings of a global survey conducted by the world health organization (WHO) in 2015 [27].…”
Section: Discussionsupporting
confidence: 78%
“…These differences could have affected the pooled OR estimates. Particularly, we should note that the chronic diseases three studies investigated were different among studies, and there was a high variation in disease incidence within the studies [37,45,50]. Furthermore, there were three studies reporting association for PPI use as risk factors for fecal carriage of drug-resistant E. coli [46,50,51], and McNulty et al…”
Section: Discussionmentioning
confidence: 98%
“…Of these, 58 studies were forwarded to full-text article screening. Of the 58 full-text articles, we identified 15 relevant articles that reported risk factors associated with drug-resistant Enterobacteriaceae (10) or E. coli (5) carriage [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Study Selectionmentioning
confidence: 99%
“…The knowledge levels among this study population are comparable to those found by Mo et al in Singapore. Their study found that 43.8% of their population believed antibiotics were for viral infections [ 15 ], while 37.8% of this study population believed antibiotics can kill viruses. However, the effect of knowledge on ESBL-EC carriage differed between both studies.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies identify avenues for intervention, they do not directly link KAP to the laboratory-confirmed presence or absence of drug-resistant bacteria. To the authors’ knowledge, only three studies to date have analyzed the link of KAP to laboratory-confirmed outcomes: (1) KAP and presence of antibiotic resistant, diarrheagenic E. coli [ 13 ]; (2) KAP of pig farmers and AMR carriage in their pigs [ 14 ], and (3) knowledge of proper antibiotic use in Singaporeans and AMR carriage among that population [ 15 ]. The present study builds on these previous studies and aims to assess how KAP of proper use of antibiotic agents is associated with laboratory-confirmed carriage of antibiotic resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%